2016
DOI: 10.1093/femspd/ftw067
|View full text |Cite
|
Sign up to set email alerts
|

Detection of intracellular bacteria in exfoliated urothelial cells from women with urge incontinence

Abstract: The role of subclinical infection in patients with urge incontinence has been largely ignored. The aim of this study was to test for the presence of intracellular bacteria in exfoliated urothelial cells obtained from the urine of patients with detrusor overactivity or mixed incontinence +/- a history of UTI, and compare this to a control group of patients with stress incontinence and no history of infection. Bacterial cystitis was assessed by routine microbiology and compared to microscopic analysis of urine b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…IBCs and other intracellular bacteria have been hypothesized to be the key populations contributing to UPEC persistence and UTI recurrence in humans, based on data from extensive studies in mouse infection models (13,16,(26)(27)(28)53) and a growing number of morphological studies in humans (33)(34)(35)(36). Substantial effort has been expended on investigating the mechanism by which UPEC establishes, maintains, and emerges from these reservoirs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IBCs and other intracellular bacteria have been hypothesized to be the key populations contributing to UPEC persistence and UTI recurrence in humans, based on data from extensive studies in mouse infection models (13,16,(26)(27)(28)53) and a growing number of morphological studies in humans (33)(34)(35)(36). Substantial effort has been expended on investigating the mechanism by which UPEC establishes, maintains, and emerges from these reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…Structures that are morphologically indistinguishable from IBCs generated in experimental mouse infections have been observed in the urine sediment of acutely infected humans, based on extensive histological, microscopic, and ultrastructural characterization, in addition to the recapitulation of IBC formation by the human-infecting strain in an experimental murine UTI model (33). Several additional studies of intracellular bacteria in both pediatric and adult UTI patients have been reported (34)(35)(36). Other studies of same-strain versus different-strain recurrence of UTI in humans have shown that some patients suffer from multiple recurrences caused by indistinguishable strains (for example, see references [37][38][39][40], consistent with IBCs being a contributor to recurrent UTI (41).…”
mentioning
confidence: 99%
“…Urine of heavily infected subjects are rich in exfoliated BECs indicating that exfoliation of BECs is a frequently employed host defense mechanism (21, 22). This capacity of infected BECs to trigger cell death is a double-edged sword as it allows for elimination of large congregates of bacteria associated with BECs but also exposes underlying cells to both toxic urine as well as any bacteria still present in the urine (23).…”
Section: Cellular Components Of the Innate Immune Response To Infectionmentioning
confidence: 99%
“…Microscopic examination of bladder biopsies revealed the presence of intracellular bacteria in 8 out of 16 patients who had LUTS in the absence of bacteriuria (38). More recent studies have confirmed and extended these findings, showing that intracellular bacteria are especially common in LUTS patients with idiopathic overactive bladder (3942). The apparent involvement of intracellular uropathogens in the etiology of LUTS for a large subset of patients is intriguing, and suggests that the optimized use of host membrane-permeable antibiotics or other therapeutics that target invasive bacteria may be valuable treatment alternatives for these individuals.…”
Section: Intracellular Uropathogens In the Human Hostmentioning
confidence: 70%